PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. PELABUHAN INDONESIA III (PERSERO) CABANG BANJARMASIN - Rahmaniah, Rahmaniah; Rusidah, Siti (Business Invention, 2016)
The purpose of this study to prove the effect of partial and simultaneous Working Environment (X1), and compensation (X2) the Employee Performance (Y) PT. Pelabuhan Indonesia III (Persero) Branch of Banjarmasin. The study population numbered 237 employees and a sample was taken 96 respondents using sampling techniques stratified random sampling. The technique of collecting data using questionnaires and data analysis used is multiple linear regression. The test results prove partial Working Environment (X1) significantly affects employee performance amounted to 34.9%, and compensation (X2) significantly affects employee performance amounted to 44.5%. While there is simultaneously a significant influence at Work (X1) and compensation (X2) the Employee Performance. The magnitude of the effect is equal to 50.0%, while 50.0% is the influence of other variables notexamined by this study. The regression equation is formed Y=23 016+0225(X1)+0422(X2)+e